IL-10-Dependent Amelioration of Chronic Inflammatory Disease by Microdose Subcutaneous Delivery of a Prototypic Immunoregulatory Small Molecule - Tabares-Guevara, Jorge H.; Jaramillo, Julio C.; Ospina-Quintero, Laura; Piedrahíta-Ochoa, Christian A.; García-Valencia, Natalia; Bautista-Erazo, David E.; Caro-Gómez, Erika; Covián, Camila; Retamal-Díaz, Angello; Duarte, Luisa F.; González, Pablo A.; Bueno, Susan M.; et al. (Frontiers in Immunology, 2021)
One of the interventional strategies to reestablish the immune effector/regulatory balance, that is typically altered in chronic inflammatory diseases (CID), is the reinforcement of endogenous immunomodulatory pathways as the one triggered by interleukin (IL)-10. In a recent work, we demonstrated that the subcutaneous (sc) administration of an IL-10/Treg-inducing small molecule-based formulation, using a repetitive microdose (REMID) treatment strategy to preferentially direct the effects to the regional immune system, delays the progression of atherosclerosis. Here we investigated whether the same approach using other IL-10-inducing small molecule, such as the safe, inexpensive, and widely available polyphenol curcumin, could induce a similar protective effect in two different CID models. We found that, in apolipoprotein E deficient mice, sc treatment with curcumin following the REMID strategy induced atheroprotection that was not consequence of its direct systemic lipid-modifying or antioxidant activity, but instead paralleled immunomodulatory effects, such as reduced proatherogenic IFNγ/TNFα-producing cells and increased atheroprotective FOXP3+ Tregs and IL-10-producing dendritic and B cells. Remarkably, when a similar strategy was used in the neuroinflammatory model of experimental autoimmune encephalomyelitis (EAE), significant clinical and histopathological protective effects were evidenced, and these were related to an improved effector/regulatory cytokine balance in restimulated splenocytes. The essential role of curcumin-induced IL-10 for neuroprotection was confirmed by the complete abrogation of the clinical effects in IL-10-deficient mice. Finally, the translational therapeutic prospection of this strategy was evidenced by the neuroprotection observed in mice starting the treatment one week after disease triggering. Collectively, results demonstrate the power of a simple natural IL-10-inducing small molecule to tackle chronic inflammation, when its classical systemic and direct pharmacological view is shifted towards the targeting of regional immune cells, in order to rationally harness its immunopharmacological potential. This shift implies that many well-known IL-10-inducing small molecules could be easily reformulated and repurposed to develop safe, innovative, and accessible immune-based interventions for CID.